Pilot study on the effectiveness of the socialmind program for the rehabilitation of social cognition following acquired brain injury - Rivas-García, Sandra; García-Bermúdez, Olga; Catena, Andrés; Caracuel, Alfonso (Frontiers in Psychology, 2024)
Background: People with acquired brain injury (ABI) often have Social Cognition (SC) deficits. Impairment of SC causes the individual to have difficulties in daily functioning and can lead to social isolation. Research aimed at rehabilitation of SC in individuals with ABI is scarce and almost always addresses only one component of this ability. Objective: This pilot study aimed to assess the effectiveness of the new “SocialMind” program in improving all core components of SC in people with ABI.To determine the effectiveness of the new "SocialMind" program in improving all components of SC in people with ABI. Method: The study included 31 participants with ABI, divided into experimental and control groups. The study spanned 44 weeks, involving an initial meeting, evaluation, training, and final assessment phases. The SocialMind program, structured into four modules, each with a duration of 30 hours, targeted each SC component through tailored exercises. The program addressed emotion recognition, social awareness, ToM, and empathy. Results: The SocialMind group demonstrated significant improvements in emotion recognition (p=.017), social knowledge (p<.001), and empathy (p=.001) compared to the control group. ToM also showed a notable improvement that approached significance (p=.057). Conclusion: This pilot study suggests that theThe SocialMind program effectively enhances three of the four core components of SC in individuals with ABI.